Acceleration of an Enzymatic Reaction in Liquid Phase Separated Compartments Based on Intrinsically Disordered Protein Domains. Issue 4 (21st February 2020) - Küffner, Andreas M.; Prodan, Marc; Zuccarini, Remo; Capasso Palmiero, Umberto; Faltova, Lenka; Arosio, Paolo
Abstract: Spontaneous liquid demixing of biomolecules appears to be an efficient strategy developed by cells to organize reactions in space and time. This process allows cells to modulate biochemical reactions by locally changing the concentration and the environment of specific components. Here, we develop a strategy to couple the formation of biomolecular liquid compartments with reactions occuring within them. In particular, we conjugate a kinase enzyme with biologically derived low complexity domains and develop synthetic micro‐reactors that locally increase the enzyme concentration up to 140‐fold. We show that these micro‐reactors are characterized by a polarity comparable to methanol which promotes recruitment of small molecules. Despite exhibiting higher viscosity with respect to the surrounding solution, the reactors are liquid‐like and allow molecular diffusion within their interior. We demonstrate that the local increase in enzyme concentration accelerates the corresponding enzymatic rate up to 5‐fold. This flexible strategy enables the generation of biomolecular micro‐reactors with enhanced reactivity, with potential applications in heterogeneous biocatalysis. Abstract : Conscious coupling of structure and function : A strategy based on biologically inspired low complexity protein domains to couple the formation of biomolecular liquid compartments with reactions occuring within them is described. We develop methods to characterize concentration, polarity, liquid‐like properties and reaction rates within these compartments, showing that the local increase in enzyme concentration accelerates the corresponding enzymatic rate up to 5‐fold. This flexible strategy enables the generation of biomolecular micro‐reactors with enhanced reactivity and with potential applications in heterogeneous biocatalysis.